2022
DOI: 10.3390/ijerph191912983
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Biochar Derived from Sewage Sludge to Promote Sustainable Agriculture and Mitigate GHG Emissions—A Review

Abstract: Sewage sludge (SS) has been connected to a variety of global environmental problems. Assessing the risk of various disposal techniques can be quite useful in recommending appropriate management. The preparation of sewage sludge biochar (SSB) and its impacts on soil characteristics, plant health, nutrient leaching, and greenhouse gas emissions (GHGs) are critically reviewed in this study. Comparing the features of SSB obtained at various pyrolysis temperatures revealed changes in its elemental content. Lower hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 171 publications
1
20
0
Order By: Relevance
“…Based on its holistic review, it is crucial to consider the socioeconomic aspects of its production and consumption (Arazo et al, 2021). Several researchers (Pandey et al, 2021;Kishor et al, 2021;Xue et al, 2021) 384.31 (Shirani et al, 2020) expensive than manufacturing costs, which include labor, storage, utility costs, and other costs (which range from 51 to 5668 US dollars per ton) (Ghorbani et al, 2022). According to the study reported by , an estimated US$195,000 is spent each year on the shipping, treatment, and disposal of SSB.…”
Section: Utilization Of Ssb For Beneficial Impacts On Socioeconomic A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its holistic review, it is crucial to consider the socioeconomic aspects of its production and consumption (Arazo et al, 2021). Several researchers (Pandey et al, 2021;Kishor et al, 2021;Xue et al, 2021) 384.31 (Shirani et al, 2020) expensive than manufacturing costs, which include labor, storage, utility costs, and other costs (which range from 51 to 5668 US dollars per ton) (Ghorbani et al, 2022). According to the study reported by , an estimated US$195,000 is spent each year on the shipping, treatment, and disposal of SSB.…”
Section: Utilization Of Ssb For Beneficial Impacts On Socioeconomic A...mentioning
confidence: 99%
“…given the benefits of applying SSB to soil, which include higher yields and decreased GHG emissions (Ghorbani et al, 2022). The research of Gievers et al (2021) showed that using biochar properly and pyrolyzing digested sewage sludge can be a green alternative to both sequestering carbon and breaking the nutrient cycle.…”
Section: Utilization Of Ssb For Beneficial Impacts On Socioeconomic A...mentioning
confidence: 99%
“…in the form of oxides, phosphates, carbonates and silicates [ 18 ]. Such properties facilitate its use in agriculture as a liming agent and an amendment abundant in some macro- and micronutrients, especially in the case of sludge and animal-derived biochars [ 20 , 21 , 22 , 23 ]. In contrast, high-temperature (>500 °C) plant-derived biochars are more commonly used to mitigate soil contamination via immobilization of heavy metals and organic pollutants [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, 70% of SS is managed by incineration. More than half of the SS in South Korea is dumped into the sea [ 6 ]. Worldwide sludge production will continue to grow due to increasing urbanization and industrialization.…”
Section: Introductionmentioning
confidence: 99%
“…This method has many advantages such as reducing sludge volume by 80%, the removal of pathogenic agents and hazardous compounds from SS, metals being immobilized in a solid residue, thus reducing their leaching, and organic and inorganic fractions being immobilized in a stabilized form of pyrolytic residues (biochar) [ 10 ]. There are many benefits of biochar (BC) production: energy production, sustainable waste recycling, carbon sequestration, improvement in soil quality, plant development, and mitigating greenhouse gas (GHG) emissions [ 6 , 11 , 12 ]. Many studies have proven that the pyrolysis of sewage sludge to biochar can be more effective than the application of raw sewage sludge in reducing the environmental risks of the potentially toxic metals involved in land application [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%